EMULGEL: A NEW APPROACH FOR ENHANCED TOPICAL DRUG DELIVERY - Yadav, Sunil Kumar; Mishra, Manoj Kumar; Tiwari, Anupamaa; Shukla, Ashutosh (International Journal of Current Pharmaceutical Research, 2016)
Emulgel is used to treat aches and pains caused by colds, headaches, muscle aches, backaches, arthritis and other conditions and injuries. The patient adherence to topical formulations is significant in relation to chronic skin diseases, like fungal infections, acne, psoriasis. Emulgel is one of the recent technology in NDDS used topically having characteristics of dual control release i.e. emulsion as well as gel. Emulgels have emerged as one of the most interesting topical delivery systems as it has dual release control system i.e. gel and emulsion. When gel and emulsion are used in combined form, the dosage form are referred as emulgel.